(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The approved indications of proton pump inhibitors (PPIs) do not include generalized acid suppression. Rather these agents should be used for various forms of gastroesophageal reflux disease (GERD), patients receiving non-steroidal anti-inflammatory drugs (NSAIDs) with high bleeding risk. Several reports are available which show that chronic inappropriate use of PPIs results in severe adverse effects. Recent systemic reviews and meta-analyses studying the prescription pattern of PPIs in India over the last two decades revealed that the PPIs are being overprescribed, and prescribed for indications other than the approved indications. With this background, the current study was planned to explore the prescription and usage pattern of PPIs in a tertiary care teaching hospital. The present study was a cross-sectional observational study conducted at the punjab institute of medical sciences, Jalandhar after obtaining Institutional Ethics Committee (IEC) approval. The prescriptions received at the pharmacy department of the hospital from different open publication distribution system (OPDs) were screened.The data regarding demographics of the patient (gender, age), the prescribing department, and the total number of drugs prescribed per prescription was collected. Further, the prescriptions were analysed according to World Health Organization (WHO) prescribing indicators. It was observed that every second prescription received in the pharmacy department was of PPIs. In total 1000 prescriptions were screened and 500 prescriptions were for PPIs. 63% of the prescriptions were from female patients and the rest of the prescriptions were from male patients. The majority of the patients (58.4%) were in the age group of 18 to 40 years. 95.2% of the prescriptions contained PPIs in fixed-dose combination (FDCs) formulation. The most frequently prescribed PPI as a mono drug was pantoprazole (2.4%).The second active pharmaceutical ingredient (API), in all the FDCs, was observed to be a prokinetic agent, either domperidone or itopride. Only 4.8% of the prescriptions were from the gastroenterology clinic. The analysis of the prescription using WHO prescribing criteria showed that the average number of drugs prescribed per encounter was 4.63 and only 0.4% of the drugs were prescribed from National List of Essential Medicines (NLEM). The drugs prescribed by generic name were 81.4% against the optimal level of 100%. It can be concluded that PPIs are being prescribed without appropriate indication in most cases. These findings suggest the need for sensitization programs for practitioners for prescribing practices and appropriate use of PPIs.